Effects of cdc42 gene knockout by CRISPR/Cas9 technology on osteochondral development in zebrafish - YANG Yunfei; LI Yi; SUN Xianding (陆军军医大学学报)
Objective To knock out cdc42 gene in zebrafish using CRISPR/Cas9 technology, and investigate the effect of cdc42 on early osteochondral development. Methods After the conservation of cdc42 gene sequence of different species was analyzed by multiple sequence alignment analysis, guide RNA of cdc42 gene was designed, and cdc42 knockout zebrafish was constructed by CRISPR/Cas9 technology. The expression pattern of cdc42 was detected by whole-mount in situ hybridization, and the chondrogenesis phenotype was observed by transgenic labeled fish line Tg (col2a1a: GFP), and vertebral mineralization was observed by alizarin red staining. Results Multiple sequence alignment analysis showed that cdc42 was highly conserved in human, mouse and zebrafish, and in situ hybridization results showed that cdc42 was expressed in a variety of tissues in the head and whole body, including mandibular cartilage. With the aid of guide RNA of cdc42, cdc42 knockout zebrafish was successfully constructed by CRISPR/Cas9 technology. The cdc42 mutants exhibited shortened body length (P < 0.01) and delayed cranial development at 3 d post fertilization, with small heads and eyes (P < 0.01), as well as delayed mandibular development. The Tg(col2a1a: GFP) zebrafish showed that the mutants presented abnormal morphology of Meckel's cartilage and ceratohyal cartilage cells, with disordered arrangement of chondrocytes and increased angle and decreased length in ceratohyal cartilage (P < 0.01). The homozygous mutants died at 10~13 d after fertilization. The results of alizarin red staining suggested delayed vertebral mineralization and reduced endochondral ossification of the mutants. Conclusion CRISPR/Cas9 technology successfully knocks out the cdc42 gene in zebrafish, resulting in delayed development of jaw cartilage, delayed mineralization of the vertebrae, and decreased endochondral ossification.